Doing economics - Smith, Peter (Routledge, 2016)
Doing Economics offers a clear and accessible guide to the nature of Economics. Unlike many other mainstream disciplines, economics is a subject that many students meet for the first time when they arrive at University to study the subject at degree level. The way economics is studied at university level can vary greatly from economics as represented in the media, but this handy beginner’s guide bridges that gap.